Technological innovation, digital citizenship and social responsibility: a narrative review on current challenges - Gago-Galvagno, Lucas Gustavo (2025)
This narrative review article has the objective of reflex on the social, ethical, and civic impacts of contemporary technological innovation, especially in the wake of the digital acceleration brought about by the COVID-19 pandemic. Based on empirical data, it addresses the effects of the widespread use of screens and the incorporation of artificial intelligence (AI) in work and educational contexts. It also analyzes the structural changes these devices have generated in the aforementioned areas and citizen participation, raising the question of what it means to be a citizen in digital environments and the challenges this entails. It also discusses emerging ethical risks—such as misinformation, surveillance, and digital exclusion—and proposes a proactive approach based on critical digital literacy, civic engagement, and participatory technological governance. It concludes with an invitation to collectively rethink social responsibility in the face of technological development, emphasizing an active role for citizens and promoting responsible use with a view to improving the quality of life and outcomes in work and educational spaces.